Pelatihan Pembuatan Smart Home di SMKN 1 Rancaekek Kabupaten Bandung - Trianto, Topan (Ma'soem University, 2024)
To prepare the younger generation to face the challenges of the digital era, SMKN 1 Rancaekek took the initiative to organize training on making smart homes for its students. This training was held in response to the need for technological skills which are increasingly important in future life. The training aims to provide an in-depth understanding of the Smart home concept, including the various components used such as sensors, controllers and other smart devices. The material delivery technique uses the PAR (Participatory Action Research) method. The results of the activity show that by providing guidance and support to students in designing and building smart home prototypes, students can make smart home technology.